18F-fluoride as a prognostic indicator of bone regeneration. (May 2019) - Mathavan, Neashan; Koopman, Janine; Raina, Deepak Bushan; Turkiewicz, Aleksandra; Tägil, Magnus; Isaksson, Hanna
Graphical abstract: Abstract: Positron emission tomography (PET) is a form of nuclear imaging, which quantitatively assesses the metabolic activity through the uptake of radioactive tracers. 18 F-fluoride is a positron-emitting isotope with high affinity for bone. Despite its potential as a non-invasive measure of bone metabolism, quantitative 18 F-fluoride PET has only been used sparsely in orthopaedic applications. It has been speculated that 18 F-fluoride PET characterizes cellular activity of bone forming cells in the early stages of the regenerative process and therefore precedes the mineralization detected by conventional computed tomography (CT). Our aim was thus to combine in vivo PET and CT to map the spatiotemporal course of bone regeneration during fracture healing using an open femur fracture model in the rat and characterize regeneration in untreated and pharmacologically treated fractures using both imaging modalities. We hypothesized that PET 18 F-fluoride tracer activity at an earlier time point is predictive of CT measured bone formation at a later time point. On the basis of the RMSE and R 2 metrics of linear regression models it was conceivable for bone volumes to be predicted up to three weeks in advance in a rodent model (RMSE: 14 mm 3 –18 mm 3, R 2 : 0.79–0.82). Moreover, the data suggested that 18 F-fluoride positron-emitting activity had the potential to separate bone formation from resorption and thus could be of interest across a wide array of orthopaedic applications. Based on this data, we conclude that 18 F-fluoride positron-emitting activity is strongly correlated to bone formation and could potentially predict the volume of bone regenerated at fracture sites. The volume of bone regenerated at a fracture site can be interpreted as a measure of the healing response and 18 F-fluoride should be further investigated as a predictive diagnostic tool to identify if bone fractures will heal successfully or result in delayed healing or non-union. Statement of Significance: We aimed to combine in vivo PET and CT imaging to map the spatiotemporal course of bone regeneration during fracture healing using an open femur fracture model in the rat and characterize regeneration in untreated and pharmacologically treated fractures using both imaging modalities. We hypothesized that PET 18 F-fluoride tracer activity at an earlier time point is predictive of CT measured bone formation at a later time point. Our data suggest that 18 F-fluoride positron-emitting activity can separate bone formation from resorption and thus could be of interest across a wide array of orthopaedic applications including as a predictive diagnostic tool to identify if fractures will heal successfully or result in delayed healing or non-union.